Risk of Injury to the LDCN and IACN During Surgical Approaches to the Foot and Ankle: an Anatomical Study using 3-Tesla Magnetic Resonance Imaging. Issue 1 (January 2022) - Shah, Vrajesh J.; Mitchell, Brendon; Ghetti, Claudio B.; Huang, Brady K.; Kent, William; Foran, Ian M.
Category: Ankle; Other Introduction/Purpose: The dorsomedial branch of the lateral dorsal cutaneous nerve (dmLDCN) and anastomotic branch to the intermediate dorsal cutaneous nerve (AICN) are at risk during foot and ankle surgery. Prior studies of the distal sural nerve on cadaveric specimens are limited by small sample size.1-7 We sought to use high-field 3-tesla (3T) magnetic resonance imaging (MRI) to examine a significantly larger cohort and obtain a more representative sample of the course of the dmLDCN and AICN. A more generalizable understanding of the course and position of these structures will aid surgeons intraoperatively in avoiding iatrogenic injury when performing the dorsomedial approach to the fifth metatarsal, as well as the sinus tarsi and extended sinus tarsi approaches for calcaneal fractures and subtalar/calcaneocuboid fusions. Methods: High-field 3T MRI studies performed between January 2015 to January 2020 were reviewed. Three blinded reviewers at a single academic center measured the coronal distances of dmLDCN and AICN from the fifth metatarsal styloid (5MS). Intraclass correlation coefficients (ICC) were calculated to assess reviewer reliability. We analyzed the upper and lower quartile ranges to evaluate the risk of iatrogenic nerve injury with standard surgical approaches. Results: A total of 125 foot and ankle 3T MRIs were measured. Intraclass correlation coefficient was excellent at 0.87 for dmLDCN to 5MS and 0.88 for AICN to 5MS. 1st and 4th quartile range for the dmLDCN to the 5MS was 0.5-0.7 cm and 0.9-1.4 cm, respectively. 1st and 4th quartile range for the AICN to the 5MS was 1.6-1.9 cm and 2.3-3.2 cm respectively. The AICN was identified in 47.2% of the images. Conclusion: The dmLDCN, AICN, and SN are vulnerable to iatrogenic injury during surgical approaches to the fifth metatarsal and calcaneus. Our 1st quartile range for the dmLDCN to the 5MS of 0.5-0.7 cm suggests that nearly 25% of our values measured by 3T MRI were lower than the reported range of 0.7-1.2 cm by Fansa, suggesting iatrogenic injury to the dmLDCN with the 'high and inside approach' to the fifth metatarsal may be higher than previously thought. The 4th quartile range of the AICN's distance from the 5MS of 2.3-3.2cm places it at risk with the sinus tarsi approach.